The South African press code and investigative journalism: an in-depth study of the Sunday Times - Ojetimi, Sefiu Akinwali (My University, 2012)
Application of the Press Code in relation to investigative journalism has become a topical issue in recent years following public criticism of breaches of the code by South African newspapers. Using the Sunday Times as a case study, this research examines the application of the Press Code to two Sunday Times stories that were publicly challenged – the Land Bank reports and the Transnet story – with a view to determine what went wrong and why. As the Press Code is a major instrument of self-regulation, the research uses the social responsibility theory of the press to provide a theoretical background that effective application of the code largely determines the credibility of this regulatory mechanism. In depth interviews and document analysis are the qualitative methods used in conducting the research. The study then draws on themes emerging from these two sources to address the research questions. Is the Press Code a set of rules which South African investigative journalists are actually familiar with? Does it inform the decisions they take? Is the Press Code seen as a help or hindrance? Can it be a force for good as a guideline for best practice? At what stage may investigative journalists have breached the Press Code and why? The findings demonstrate that investigative journalists at South African newspapers are aware of the Press Code and have “a fair idea” of what it is all about but lack the basic knowledge of its content to guide them in making informed decisions in their day-to-day practice. The findings also demonstrate that breaches of the Press Code in the Land Bank and Transnet stories were largely due to failure to properly apply the Code. Among causes of the breaches are the failure of the gatekeeping function, failure to get the views of subjects of reportage and the pressure of deadlines. The study also shows that effective application of the code could help keep journalists within reasonable limits and standards. Sufficient knowledge and conscientious application of the Press Code could also prevent breaches. If well managed by journalists and the industry, correct application of the Press Code could be of great help and a force for good as a guide for best practice of the profession. It could also protect the self-regulation system from its critics and the print media generally from criticisms of shabby journalism.
M.A. University of the Witwatersrand, Faculty of Humanities (Journalism and Media Studies), 2012